Structure and Membrane Targeting of the PDZD7 Harmonin Homology Domain (HHD) Associated With Hearing Loss - Lin, Lin; Wang, Huang; Ren, Decheng; Xia, Yitian; He, Guang; Lu, Qing (Frontiers in Cell and Developmental Biology, 2021)
Usher syndrome (USH) is the leading cause of hereditary hearing-vision loss in human. PDZD7 (PDZ domain-containing 7) was reported to be a modifier and contributor to USH. PDZD7 co-localizes with USH2 proteins in the inner ear hair cell, essential for ankle-link formation and stereocilia development. PDZD7 contains three PDZ domains and a low-complexity region in the middle of two PDZ domains, which has been overlooked in the previous studies. Here we identified a well-folded HHD (Harmonin Homology Domain) domain from the middle region and solved PDZD7 HHD structure at the resolution of 1.49 angstrom. PDZD7 HHD adopts the same five-helix fold as the other HHDs found in Harmonin and Whirlin. But, in PDZD7 HHD, a unique α1N helix occupies the canonical binding pocket, suggesting a distinct binding mode. Moreover, we found PDZD7 HHD domain can bind with lipid and mediate the localization of PDZD7 to plasma membrane in HEK293T cell. Intriguingly, a hearing-loss human mutation at the N-terminal extension region of HHD can disrupt the lipid binding ability of PDZ7 HHD, suggesting the HHD-mediated membrane targeting is required for the hearing process. The structural and biochemical characterization on PDZD7 HHD region provides mechanistic explanations for human deafness-causing mutations in PDZD7. The structure will also facilitate biochemical and functional studies of other HHD domains.